Parasitism and mating of Diaeretiella rapae (Hymenoptera Aphidiidae) in an uncontrolled environment - Kant, R.; Minor, M.A.; Trewick, S.A.; Sandanayaka, W.R.M. (New Zealand Plant Protection, 2010)
Parasitism and mating activities of Diaeretiella rapae were studied in a shadehouse under ambient environmental conditions during September (early spring) and November (late spring) Before collecting the data the parasitoid and its aphid host colonies were left to develop undisturbed on cabbage seedlings for 3 months in about 25 m2 area The plants were highly infested with aphids (average 27225 aphids/plant) and parasitism by D rapae varied between 25 and 36 during the study period There was no significant change in parasitism rate during the 10week study period (P069) Adult parasitoids emerged from aphid mummies at a rate of more than 90 with a higher number of females than males The mean female/male parasitoid sex ratio was greater in the second 5week (late spring) than the early 5week period (early spring) (P